The importance of landscape for identity in the aftermath of devastation and dislocation past and present - Duijvenvoorde, Julia van; Fairclough, Graham; Lekakis, Stelios; Meier, Thomas; Turner, Sam; Vuletic, Nikola (Journal of European landscapes, 2023)
Abstract “Devastation, Dislocation and (re-)Settlement: Breaking/replacing the people-place connection in landscape” is an interdisciplinary research project and network funded by the German Research Foundation (DFG) and the Arts and Humanities Research Council (AHRC), running from 01.01.2022 to 31.12.2024. The project is jointly conducted by the Käte Hamburger Center for Apocalyptic and Post-Apocalyptic Studies (University of Heidelberg, Germany) and the McCord Centre for Landscape (Newcastle University, UK), both interdisciplinary research institutes focused on studying the complex intertwinement of humans with their environment.
Gesehen am 23.08.2024